HUBUNGAN TINGKAT PENGETAHUAN MENGENAI RISIKO KEHAMILAN DENGAN PERILAKU SEKSUAL REMAJA DI KELURAHAN MANGGA DUA SELATAN - Lestari, Puspita Hanggit (Jurnal Kesehatan Holistic, 2017)
Sexual problems in adolescents are not limited to physical problems but also to psychic feelings of curiosity to sexual problems. The deviation of adolescent sexual behavior has an impact on the risk of adolescent reproductive systems, including the risk of pregnancy outside marriage, abortion in teenage pregnancy, vulnerable to HIV / AIDS and various sexually transmitted diseases, reproductive tract disorders and psychosocial disorders. The purpose of this study is to know the relationship of knowledge level about pregnancy risk with adolescent sexual behavior. This cross-sectional study used purposive random sampling technique with 78 respondents of high school students in West Jakarta. The study assessed the knowledge level of pregnancy risk and adolescent sexual behavior using questionnaires. The results showed that there was a significant relationship between the level of adolescent knowledge about the risk of pregnancy in adolescence with adolescent sexual behavior. Based on that the teenagers need help and monitoring parents in understanding the correct info related to sexuality.